2020
DOI: 10.1016/j.cell.2020.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the Sense of Touch Using a Sensorimotor Demultiplexing Neural Interface

Abstract: Highlights d Following spinal cord injury, subperceptual touch signals affect the human motor cortex d A brain-computer interface uses subperceptual signals to restore the sense of touch d Sensorimotor function is further enhanced using demultiplexed sensorimotor signals d Touch-regulated grip force can automate movement cascades and grip reanimation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 88 publications
(210 reference statements)
3
78
0
Order By: Relevance
“…Accurate but slow movements can be generated for high-dimensional artificial hands with wrist and digits; however, the accuracy is challenged by changing limb posture and orientation. One potential solution is the use of closed-loop control systems that provide not only the forward control of prosthetic, but also incorporate the sensory feedback within neuroprosthetics (Charkhkar et al, 2020; Ganzer et al, 2020; Hughes et al, 2020). The closed-loop control system that takes into account muscle forces will likely require accurate representation of musculoskeletal actions, which are essential for the description of both muscle forces and sensory signals responsible for proprioception.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate but slow movements can be generated for high-dimensional artificial hands with wrist and digits; however, the accuracy is challenged by changing limb posture and orientation. One potential solution is the use of closed-loop control systems that provide not only the forward control of prosthetic, but also incorporate the sensory feedback within neuroprosthetics (Charkhkar et al, 2020; Ganzer et al, 2020; Hughes et al, 2020). The closed-loop control system that takes into account muscle forces will likely require accurate representation of musculoskeletal actions, which are essential for the description of both muscle forces and sensory signals responsible for proprioception.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have demonstrated retained sensory pathways in some patients deemed clinically complete SCI, termed sensory discomplete. [31][32][33] Patients with clinically complete injuries could be evaluated prior to surgery for the presence of sensory discomplete lesions (e.g, fMRI activity present for finger sensations), which could benefit from the same approach described in this study.…”
Section: Limitations and Next Stepsmentioning
confidence: 99%
“…Such fine-resolution recordings have enabled intuitive control of high DOF robotic arms (Wodlinger et al, 2015 ) and functional electrical stimulation (FES) systems (Colachis et al, 2018 ) by people with quadriplegia. MEAs can also provide the necessary somatosensory feedback-control to enhance grip performance of high DOF robotic arms (Flesher et al, 2017 ) and advanced FES orthotics (Ganzer et al, 2020 ). This review focuses on recording disruptions that affect MEA BMI performance and limit their use.…”
Section: Introductionmentioning
confidence: 99%